Development of Electrical Circuit Display Panel for Light Vehicle Turn Signal Lights as a Learning Media for Vocational School Students - Rival, Ahmad; Abubakar; Fatwa, Islami; Pratiwi, Rani Ardesi (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to develop a demonstration panel for the electrical circuit of light vehicle turn signal lights as a learning medium. The purpose of making this demonstration panel is to describe the process of making a demonstration panel for the electrical system of turn signal lights on light vehicles, to describe the feasibility test of the electrical circuit demonstration panel for light vehicle turn signals and to describe students' responses to the electrical system demonstration panel for turn signal lights on light vehicles. This research uses the Research and Development method. The subjects in this research are material experts and media experts as well as students, and the objects are teaching materials and students. The instruments used are: observation, questionnaires and documentation. Research procedures include potential and problems, data collection, product design, design validation, design improvement, and product testing. The data analysis technique used is a descriptive analysis technique by explaining the results of making the product in the form of a learning media display panel, testing the validity and suitability of the product to be implemented in lighting systems and light vehicle instrument panels. 1) The results of the process of making electrical circuit display panels for light vehicle turn signal lights as a learning medium have been successfully described in detail, including the steps and components used. 2) The results of the demonstration panel feasibility test after being validated by material expert I scored 93.75%, and material expert II gave a score of 96.87%. Meanwhile, the feasibility results of the media expert panel I gave a score of 100%, and media expert II gave a score of 95.83%. 3) The results of students' responses to the demonstration panel received a very good response, the overall score obtained was 90.38%, which is very suitable.